Media Efektif dalam Meningkatkan Partisipasi Imunisasi Anak: Scoping Review - Syiadatika, Afifatus; Camelia, Rini; Melia inggriani, Dela (Poltekkes Kemenkes Kupang, 2024)
Background: Immunization is an effort to provide immunity to children by administering vaccines into the body through injections, which include DPT, Measles, and Rubella vaccines. These vaccines stimulate the production of antibodies, enabling children to avoid specific diseases. The provision of complete immunization in children is influenced by several factors, including occupation, knowledge, attitudes, and family education. Objectives: This study aims to identify the most influential media in delivering health education to improve full immunization participation in children. Methods: The scoping review was conducted using the PRISMA ScR framework checklist adapted from the 2018 guidelines. Results: From a selection of 2,501 articles based on inclusion and exclusion criteria, the review identified eight relevant articles. The influential media in delivering health education to improve full immunization participation in children were categorized into three themes: types of media, benefits of media use, and barriers to media utilization. Among various media, SMS proved to be the most impactful in increasing children's immunization rates. This is attributed to its ease of use, cost-effectiveness, and the fact that it does not require an internet connection, making it accessible in all areas.